2017
DOI: 10.1016/j.landurbplan.2016.05.027
|View full text |Cite
|
Sign up to set email alerts
|

Green infrastructure for urban climate adaptation: How do residents’ views on climate impacts and green infrastructure shape adaptation preferences?

Abstract: h i g h l i g h t s• Novel socio-cultural valuation framework for green infrastructure and climate impacts.• People are more aware of present-day heat waves but more alarmed by future flooding.• People tend to prefer diverse, familiar and visually attractive adaptation measures.• Environmental education can increase support for effective adaptation measures.• Results help planners prioritize effective and desired green infrastructure designs. a r t i c l e i n f o b s t r a c tCities are particularly prone to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
136
1
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 258 publications
(174 citation statements)
references
References 34 publications
11
136
1
6
Order By: Relevance
“…As Derkzen et al [12] point out, understanding people's views on climate change and adaptation options is vital for prioritizing policy responses for climate adaptation. However, both Geneletti et al [9] and Derkzen et al [12] indicate the need for assessments and stronger evidence of the benefits and co-benefits of nature-based solutions versus other options. In addition, Geneletti et al [9] also points at the importance of mainstreaming and integrating nature-based climate adaptation measures in the urban planning process.…”
Section: Discussionmentioning
confidence: 99%
“…As Derkzen et al [12] point out, understanding people's views on climate change and adaptation options is vital for prioritizing policy responses for climate adaptation. However, both Geneletti et al [9] and Derkzen et al [12] indicate the need for assessments and stronger evidence of the benefits and co-benefits of nature-based solutions versus other options. In addition, Geneletti et al [9] also points at the importance of mainstreaming and integrating nature-based climate adaptation measures in the urban planning process.…”
Section: Discussionmentioning
confidence: 99%
“…Environmental factors may include decreasing pollution levels [6,7,15,51], improvements for water run-off [6, 7,15], or the general value of trees [51]. The attenuation of stormwater run-off and pollution are provided with the adoption of green roofs, and a study of Melbourne Australia showed the potential benefits derived from the widespread adoption in retrofits [57,58].…”
Section: Technologies For Improved Environmental and Storm Water Manamentioning
confidence: 99%
“…Studies showed that WTP might be negative or nil if respondents were dissatisfied with public GI standards, which is practically experienced with municipally owned areas such as parks or walking areas [7]. Mell et al's [45] results showed that bearing costs for the maintenance of GI may have a negative effect on WTP.…”
Section: Quality and Aestheticsmentioning
confidence: 99%
“…Results indicated that while respondents were generally aware of the impacts of climate change, they were not aware that green infrastructure could mitigate these impacts. After being informed of the climate change adaptation capacity of green infrastructure, respondents opted for the most effective strategies (Derkzen et al, 2017). Surveys of resident perception of green infrastructure for the mitigation of climate change stresses in Gold Coast City (Australia) found that, despite vulnerability to heat stress, relatively disadvantaged residents, "are no more concerned about climate change;…”
Section: Climate Change and Resiliencementioning
confidence: 99%